Analysis of years of life lost due to premature cancer mortality in the Russian Federation - Zh. V. Khailova; A. D. Kaprin; V. V. Omelyanovsky; D. N. Pustovalov; Yu. A. Agafonova; V. O. Kusakina; S. A. Ivanov; P. V. Shegai (Сибирский онкологический журнал, 2023)
Background. Burden of disease estimation allows analyses to be carried out integrally, including cause and effect assessment. the rate of life years lost due to premature mortality is part of the burden of disease analysis. given that the burden of cancer is steadily increasing, analysis of the number of years lost makes it possible to identify new strategic directions, as well as to adjust decisions already made, in the health care of cancer patients.Purpose: to estimate the loss of life expectancy as a result of premature mortality from cancer in the population of the Russian Federation.Material and Methods. the analysis was carried out using international statistical databases for disease burden estimation, databases of the Federal state statistics service (Rosstat). to determine the target groups of priority reduction of mortality from neoplasms in the Russian Federation, an estimation of the lost years of life expectancy as a result of premature mortality in the form of the e† (e-dagger) indicator was carried out. the analyzed period of the study was 2010–2019.Results. the Russian Federation is characterized by the smallest share of losses from cancer in the structure of losses from all causes of death compared to the analyzed countries (Japan, France, germany, latvia, lithuania, estonia). However, the share of losses has been intensively increasing for 10 years (in 2010 – 14.79 %, in 2019 – 17.54 %). in comparison with the analyzed countries, Russia is more characterised by losses from cancer at a younger age, with the highest value of life years lost in the age group 60–64 years. the age-standardized number of years lost in men in Russia is 67.1 % higher than in women. in the age group from 25 to 49 years of age, the loss of life expectancy due to cancer in women is higher and accounts for 0.4 years (or 19 %) of all losses, which is not typical of other age groups in which losses in men prevail. A significant regional differentiation of mortality in the constituent entities of the Russian Federation has been revealed, which is also reflected in the number of years lost.Conclusion. the potential of preventive strategies in the Russian Federation has not been fully realized – the loss of life years in young and middle age requires the correction of measures to improve preventive services and oncological care. the revealed regional differentiation allows us to identify regions with high losses for priority solutions.